The beneficial impacts of functional groups of CNT on structure and gas separation properties of PEBA mixed matrix membranes. (February 2020) - Amirkhani, Farid; Mosadegh, Minoo; Asghari, Morteza; Parnian, Mohammad Javad
Abstract: Incompatibility between filler and polymer chains accompanied by particle agglomeration has a detrimental effect on the performance of mixed matrix membranes (MMMs). To obviate intermolecular forces of different additives, functional groups (-COOH, –NCO, and –NH2 ) were grafted on the surface of multi-walled carbon nanotubes (MWCNTs) which were then incorporated as fillers in the poly(ether-block-amide) (PEBA) polymeric matrix in the range of 0.1–1 wt% loading. CO2 permeability and ideal CO2 /N2 and CO2 /CH4 selectivity of MMMs was compared with the neat membrane, and the results revealed favorable enhancement and surpassed CO2 /N2 Robeson's upper bound under 4–10 bar in the range of 15–55 °C. Mixed gas separation performance of MMMs, which is of vital importance in industrial applications, was also investigated. The results indicate that MWCNT-NCO created superior grafts with the polymer chains, and MMMs with this additive had a better gas separation performance with high mechanical and thermal stability. Highlights: Functionalized fillers overcome the tendency of CNT agglomeration. CO2 permeability and permselectivity of the MMMs were enhanced simultaneously. The plasticization resistance of P8CNT-COOH decreased due to acid functionalization. At the lower temperature and higher pressure, MMMs had better permeation. NCO as a functional group improved physiochemical properties and gas separation.